Long-standing temporomandibular joint dislocation treated by intraoral condylectomy: a case report and review of the literature - Ryo Uetsuki; Shigehiro Ono; Misato Tada; Satoshi Okuda; Masaaki Takechi (Journal of Medical Case Reports, 2022)
Abstract Background Noninvasive management by closed reduction is a desirable treatment for temporomandibular joint dislocation. However, reduction of long-standing temporomandibular joint dislocation is often difficult. Various conservative treatments have been attempted, but these often render poor outcomes. This article reports the case of long-standing temporomandibular joint dislocation that was successfully closed using intraoral condylectomy. Case presentation A 69-year-old Japanese man who sustained an injury in a car collision was unable to close his mouth. Owing to the diagnosis of long-standing temporomandibular joint dislocation, intraoral condylectomy was performed. In the case of temporomandibular joint dislocation, it is convenient to reach the condyle from the oral cavity because sufficient opening is maintained. The condyle can be clearly visualized using an approach similar to sagittal split ramus osteotomy, and the operation using surgical instruments can be facilitated by resecting the coronoid process. By separating the surrounding soft tissue and pulling the cut condyle with sufficient visual field, the condyle can be resected while addressing the hemostasis. During the 12-month postoperative follow-up period, no temporomandibular joint dislocation recurred and the occlusion remained stable. Conclusions The limited intraoral incision of this surgical technique provides sufficient access for condylectomy. The results of this case report suggest that condylectomy by intraoral approach could become the treatment of choice for long-standing temporomandibular joint dislocation.